Fibroma of Epiglottis - Karki, P; Gurung, U; Baskota, DK (Nepalese Journal of ENT Head and Neck Surgery, 2011)
Key words: fibroma; epiglottis; larynx; excision DOI: 10.3126/njenthns.v1i1.4733 Nepalese J ENT Head Neck Surg Vol.1 No.1 (2010) p.19-20